Myeloid Sarcoma presenting as orbital mass: a diagnostic challenge - Chaudhury, Supriyo Roy; Jain, Bhawna Bhutoria; Jain, Chetan; Chattopadhyay, Sarbani (Annals of Pathology and Laboratory Medicine, 2014)
Myeloid sarcomas (MS) are extramedullary myeloid neoplasm and can present as solitary tumor without bone marrow and blood involvement.The rarity of the condition, its atypical presentation & difficulty to diagnose it in routine histopathological sections pose a diagnostic challenge to both pathologists and clinicians which prompted us to present this case. A case of myeloid sarcoma occurring as orbital mass in a 60 year old is presented here. The finding as seen on a cytological smear, histological features and immunohistochemistry is discussed. Strong clinical suspicion is prerequisite. The pathologist should examine the slide carefully so that the diagnosis is not missed. Presence of eosinophilic myelocyte provides a diagnostic clue.